Entrepreneurial Responses to Chronic Adversity The Bright, the Dark, and the in Between - Shepherd, Dean A.; Parida, Vinit; Wincent, Joakim (Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This open acess book extends recent work on entrepreneurship in response to adverse events to explore entrepreneurial responses by people who face chronic adversity more deeply. Instead of focusing on the sort of responses intended to destroy the institutions that create and sustain chronic adversity, the authors are interested in how individuals use entrepreneurial action to find a way within these adverse constraints to improve their lives. They explore the positive outcomes arising from these entrepreneurial actions for the entrepreneurial actor and their family members as well as the negative consequences of these entrepreneurial responses to chronic adversity - outcomes that diminish others' well-being. The book relies on the lived experiences of those facing chronic adversity to provide insights into the bright - and dark - sides of entrepreneurship and the complexity of these relationships. It will serve as a valuable resource to scholars seeking to understand how entrepreneurial action is conceived and implemented by those facing challenging resource-poor environments.